Influence of unloading and loading stress cycles on the creep behavior of Darley Dale Sandstone. (December 2018) - Chen, Chongfeng; Xu, Tao; Heap, Michael J.; Baud, Patrick
Abstract: We report uniaxial experiments on Darley Dale Sandstone designed to reveal the effect of stress perturbations during deformation at a constant stress. To guide the target creep stress to be used in our unloading and loading creep tests, we first performed a series of uniaxial compression tests and conventional creep tests. Our unloading and loading creep tests show that cycling the stress transiently increases the strain rate and the rate of AE activity. We interpret this behavior as the result of a sharpening of microcracks during the stress cycling, thereby increasing the efficiency of stress corrosion cracking. After several hours, however, the microcracks return to their "blunt" state and the rates of deformation return to their initial values. Since the loading cycles reload the sample back to the initial creep stress, our experiments do not therefore comply with the Kaiser "stress memory" effect, which stipulates that additional microcrack damage is imparted only when a sample is exposed to a stress higher than previously experienced. Our experiments also suggest that stressing rate (in the range 0.05 and 5 MPa/s) does not influence the increase in strain rate and AE rate following a particular stress cycle. We conclude that the stress perturbations that commonly occur during mining practices may promote the failure of the pillars and/or surrounding rock in active mines.